Matemática em Libras - SOUZA, Djane da Silva (Universidade Federal do Tocantins, 2023)
This research starts from a reality in which the classroom appears increasingly diversified, where it is the duty of the school together with the teachers to ensure the success of all students, each one in particular, adapting to the different needs of each student., in the case of this particular work, adapting to our target audience, the deaf student, in search of a reconfiguration of the school environment through digital technologies. Therefore, we seek to highlight the importance of searching for various pedagogical strategies for a technological and mathematical fluency of such students through Brazilian Sign Language. This research aims to produce a Didactic Sequence adapted to the profile of the inclusive school, and the production of a game digital, both in Learning Objects (LO) format, working simultaneously LIBRAS and mathematical concepts, which explore an interactive environment that provides visual and playful, committed to gaining interest and participation on the part of students. The methodology used in this research has a qualitative exploratory approach, in order to validate the constructed DS, in addition to being based on current laws and guidelines. Produced the LOs according to the essential characteristics that best fit the established objectives, related to the experiences in academic training in the area of TDIC, it is clear that Scratch becomes a powerful ally in the development of interactive and dynamic environments, of visual and motor character, essential in the learning of deaf students inserted in the inclusive classroom.